Prevalence of sleep disorders and their association with poor academic performance among medical students of Punjab, Pakistan: a cross-sectional study - Fareh, Zohad; Asif, Muhammad; Abdullah Tariq, Muhammad; Javed, Rabia; Nisar, Mudasar; Batool, Maryum; Gulzar, Mashal; Fareen, Ayesha; Hassan, Ahmad; Akhtar, Samia Gull (International Journal Of Community Medicine And Public Health, 2026)
Background: Medical students face heavy workloads, overnight duties, and high stress, which can impair sleep and academic performance. Objectives were to assess the prevalence of sleep disorders among medical students in Punjab, Pakistan, and their association with academic performance. Methods: From January to June 2025, MBBS students at 16 medical colleges in Punjab were invited to complete the English SLEEP-50 questionnaire (pilot-tested on 30 students). Of 500 invitees, 345 (69%) participated. Demographics, BMI, sleep patterns, and annual academic percentage were self-reported. Sleep duration was classified as short (<6 hours), normal (6-8 hours), or long (>8 hours). Academic performance was grouped as below average (50-69%), excellent (70-85%), or outstanding (>85%). Chi-square tests and binary logistic regression- adjusting for all the variables in the model- were used to identify factors independently associated with poor performance (<70%). Results: Mean age was 21.85±3.1 years; 30% female; mean BMI 22.3±3.6 kg/m2. Seventy-five percent screened positive for at least one sleep disorder: narcolepsy (62%), restless legs syndrome (29%), and insomnia (18%). Adjusted analysis showed obesity (OR=13.16; 95% CI 3.08-55.56; p<0.001), insomnia (OR=5.24; 95% CI 2.19-12.50; p<0.001), narcolepsy (OR=5.00; 95% CI 1.93-12.99; p=0.001), and male gender (OR=4.20; 95% CI 1.63-10.84; p=0.003) as significant factors. Conclusions: Sleep disorders are common among Punjab’s medical students. Obesity, insomnia, narcolepsy, and male gender were independently associated with poor academic performance. Early screening and targeted interventions are needed to improve student well-being and achievement.